HUBUNGAN PENGETAHUAN DAN PERILAKU IBU DENGAN KEJADIAN STUNTING PADA BALITA 24-59 BULAN - Eva Oktariani; Yulnefia; ratih ayuningtiyas; vivi vazelah (Jurnal Ilmu Kesehatan Abdurrab, 2023)
This study aims to determine the relationship between knowledge and behaviour of maternal in fulfilling balanced nutrition with the incidence of stunting in toddlers aged 24-59 months in the work area of ​​the Kandis Health Center, Kandis District, Siak Regency in 2024. This study used a cross-sectional research design with a sampling technique using probability sampling with the proportionate stratified random sampling method, with a sample size of 229 respondents. The analysis used was univariate and bivariate analysis with the Chi-Square statistical test. From the results of the data analysis, a significant relationship was found between maternal knowledge in fulfilling balanced nutrition with the incidence of stunting in toddlers aged 24-59 months in the work area of ​​the Kandis Health Center, Kandis District, Siak Regency in 2024 with a p-value of 0.023 and a PR of 6.456. In addition, a relationship has been found between maternal behaviour (p-value 0.006) and maternal behavior (p-value 0.006) in fulfilling balanced nutrition with the incidence of stunting for PR values ​​of behavior of 10.114. Maternal knowledge is related to fulfilling balanced nutrition and are risk factors for stunting in toddlers aged 24-59 months in the work area of ​​the Kandis Health Center, Kandis District, Siak Regency in 2024. Not only that, maternal behavior in fulfilling balanced nutrition are related and are risk factors for stunting in toddlers aged 24-49 months in the work area of ​​the Kandis Health Center, Kandis District, Siak Regency